Застосування індексу флуктуючої асиметрії для районування території дендрологічного парку “Олександрія” за величиною техногенного забруднення - Dragan, N.V.; Dojko, N.М.; Dragan, G.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Possibility of using of fluctuating asymmetry index (on leaves of Partenocissus quinqiefolia (L.) Planch.) for division territory of Dendrology Park Alexandria into areas according to the level of technogenic pollution was studied. The status of two park areas as the most anthropogenic polluted was confirmed new area in the north-east part of the park was revealed.